2021
DOI: 10.1111/jnu.12741
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a brief family strengths‐oriented therapeutic conversation intervention for patients with schizophrenia and their caregivers

Abstract: Purpose: To examine the effects of a brief family strengths-oriented therapeutic conversation (FAM-SOTC) intervention on symptom severity of patients with schizophrenia and family coping and caregiver burden for family caregivers. Design:A quasi-experimental research design with repeated measures. Methods:A convenience sample of 72 dyads of patient-family caregivers was recruited from randomized inpatient psychiatric rehabilitation units in a psychiatric hospital in Taiwan. Sixty-one patient-family caregiver d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…For example, in the RCT conducted by Ågren et al (2019), the FAM-TC improved the stress of families with a critically ill member after 3 months of the intervention, but not after 12 months. Similarly, Hsiao et al (2022) found that the FAM-TC improved caregivers' burden of patients with schizophrenia and their family caregivers at intermediate and 1 month, but not at 3 months. This lack of sustainability over time of the effectiveness of the family interventions was mainly shown in the measured outcomes that referred to the negative effects of the disease.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…For example, in the RCT conducted by Ågren et al (2019), the FAM-TC improved the stress of families with a critically ill member after 3 months of the intervention, but not after 12 months. Similarly, Hsiao et al (2022) found that the FAM-TC improved caregivers' burden of patients with schizophrenia and their family caregivers at intermediate and 1 month, but not at 3 months. This lack of sustainability over time of the effectiveness of the family interventions was mainly shown in the measured outcomes that referred to the negative effects of the disease.…”
Section: Discussionmentioning
confidence: 84%
“…Participation acceptance rates varied among studies, ranging from 49% (Jonsdottir et al, 2021a) to 90% (Aass et al, 2020; Åberg Petersson et al, 2021; Holst-Hansson et al, 2020). In the same way, the intervention completion rates varied, ranging from 50% (Ågren et al, 2019; Broekema et al, 2021) to 100% (Hsiao et al, 2022; Jonsdottir et al, 2021a; Petursdottir et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, some intervention measures could effectively decrease the burden of care and increase self-efficacy, such as an interpersonal psychotherapy technique and psychoeducation 14 , a brief family strengths-oriented therapeutic conversation intervention 69 and a group psychoeducational intervention. 70 A previous study found that higher levels of hopefulness in the family caregiver was associated with low family caregiver's burden.…”
Section: Discussionmentioning
confidence: 99%